If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(z + -1i) = 0 Reorder the terms: ln(-1i + z) = 0 (-1i * ln + z * ln) = 0 (-1iln + lnz) = 0 Solving -1iln + lnz = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-1lnz' to each side of the equation. -1iln + lnz + -1lnz = 0 + -1lnz Combine like terms: lnz + -1lnz = 0 -1iln + 0 = 0 + -1lnz -1iln = 0 + -1lnz Remove the zero: -1iln = -1lnz Divide each side by '-1ln'. i = z Simplifying i = z
| 0,42=25/x | | 5a-32=48 | | (5r-30)=0 | | -30/5r | | 9x+5=17+x | | 86=2x+2y | | 1*3x=3 | | 7x+2=3(x+1) | | x^4-3x^3-4x^3+x^2+5x^3+x-3= | | X-12+x+10+X=163 | | 6x^2-11x-60=0 | | 17-6x=11-5x | | (-7-4)+13=2 | | 14y-15=17 | | 1.5x+38/3=4/3x-0.75 | | Abc=bca-acb | | Abc=bca-ach | | 9s^2+25=0 | | 3t(t-6)= | | 8x+9=7x+8 | | (3x-31)=(2x+14) | | 10x+5=9x-5 | | 38/32 | | 2a^3+3a^2-8a=0 | | 8*x-(1000/X^2)=0 | | (3y-4)(y+2)(y+1)=0 | | 6x-3=(3x-2) | | -2916=-4n^(3/2) | | x^3-4x^2+4x-3=(x-3) | | 4+3sin(x)=2.5 | | -14x^2+81x=0 | | 2(10-2n)^(1/5) |